(untitled) (Gragoatá, 2016)
This article focuses on four paradigmatic cases of travelers. The central part concerns Dina Lévi-Strauss who gave the first course on modern ethnography in Brazil. She transfered the very latest: her projects include the founding of an ethnographic museum modeled on the “Musée de l`Homme”. Claude Lévi-Strauss and Fernand Braudel traveled to São Paulo as members of the French mission, which played an important role in the founding of the University of São Paulo. For political reasons Claude Lévi-Strauss’ contract at the University was not renewed in 1937. Blaise Cendrars was already a famous poet when he crossed the Atlantic in 1924. Fascism in Europe and World War II interrupted the careers of these four travelers as well as their interchanges with Brazil and their Brazilian friendships. But Brazilian experiences of Claude Lévi-Strauss and Braudel are crucial for their successful careers, after 1945. —————————————————————————————————- Travessia transatlântica nos anos 1920 e 1930: as trajetórias da vanguarda poética e científica europeia no Brasil O artigo trata de quatro casos paradigmáticos de viajantes. A parte central está dedicada a Dina Lévi-Strauss, quem ministrou o primeiro curso de etnografia moderna no Brasil, apresentando nele o que havia de mais recente em sua época; seus projetos ainda incluíam a fundação de um museu etnográfico concebido a partir do modelo do “Musée de l’Homme”. Por sua vez, Claude Lévi-Strauss e Fernand Braudel viajaram a São Paulo como membros da Missão francesa, que teve um papel importante na fundação da Universidade de São Paulo, mesmo que, por razões políticas, o contrato de Claude Lévi-Strauss não tenha sido renovado pela Universidade em 1937. Antes deles, Blaise Cendrars era já um poeta famoso quando cruzou o Atlântico em 1924. O fascismo na Europa e a Segunda Guerra Mundial interromperam as carreiras destes quatro viajantes tanto quanto seus intercâmbios com o Brasil e com seus amigos brasileiros. Contudo, as experiências que Claude Lévi-Strauss e Braudel levaram a cabo no Brasil foram cruciais para o sucesso de suas respectivas carreiras após 1945. — Artigo em inglês.